2013
DOI: 10.3389/fimmu.2013.00200
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies and Their Receptors: Different Potential Roles in Mucosal Defense

Abstract: Over recent years it has become increasingly apparent that mucosal antibodies are not only restricted to the IgM and IgA isotypes, but that also other isotypes and particularly IgG can be found in significant quantities at some mucosal surfaces, such as in the genital tract. Their role is more complex than traditionally believed with, among other things, the discovery of novel function of mucosal immunoglobulin receptors. A thorough knowledge in the source and function and mucosal immunoglobulins is particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 111 publications
2
72
0
1
Order By: Relevance
“…T cell-dependent and T cell-independent pathways, and secreted immunoglobulins at LP are then transported to the lumen by immunoglobulin receptors (Strugnell and Wijburg, 2010;Horton and Vidarsson, 2013). We showed the lymphocyte populations including intestinal B cells and B220 − IgA + cells (which represent plasma cells) were not significantly different and IgA secreting cells in LP were not also different by using ELISPOT assays (data not shown).…”
Section: Syntenin-1mentioning
confidence: 45%
See 2 more Smart Citations
“…T cell-dependent and T cell-independent pathways, and secreted immunoglobulins at LP are then transported to the lumen by immunoglobulin receptors (Strugnell and Wijburg, 2010;Horton and Vidarsson, 2013). We showed the lymphocyte populations including intestinal B cells and B220 − IgA + cells (which represent plasma cells) were not significantly different and IgA secreting cells in LP were not also different by using ELISPOT assays (data not shown).…”
Section: Syntenin-1mentioning
confidence: 45%
“…Additionally, recent studies have shown that mucosal IgM and IgG can also provide humoral protection from various pathogens (Horton and Vidarsson, 2013;Saeland et al, 2003;Stapleton et al, 2011). On the other hand, mucosal IgG or IgM production is excessively increased in patients with an inflammatory bowel disease such as ulcerative colitis and Crohn's disease (Helgeland et al, 1992;Macpherson et al, 1996;Thoree et al, 2002).…”
Section: Syntenin-1mentioning
confidence: 98%
See 1 more Smart Citation
“…(a), a significant increase in the mean fluorescence intensity value due to parasite‐bound IgA was observed in tachyzoites incubated with IgA‐NcMP/CpG compared with that of parasites incubated with IgA‐CpG, so confirming the specificity of the antibodies raised by immunization. The agglutination of pathogens is one recognized effector function of IgA in the intestinal mucosa, so preventing their attachment to host cells . To assess the agglutinating capacity of the intestinal IgA produced on i.n.…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophil granulocytes, similar to other leukocytes of myeloid origin, express the FcaRI, which is specific for IgA. However, this receptor has (5,11,12,51), whereas IgA complexed with Ag triggers multiple proinflammatory activities, including neutrophil recruitment, ROS release, and Ab-dependent cytotoxicity (11,12). For subepidermal blistering diseases, only indirect evidence exists for the proinflammatory activity of IgA autoantibodies.…”
Section: Discussionmentioning
confidence: 99%